Rapid disease progression on immune checkpoint inhibitors in young patients with stage IV melanoma - Machiraju, Devayani; Schäfer, Sarah; Beckhove, Philipp; Roth, Jasmin; Schulz, Carsten; Hassel, Jessica C. (Frontiers in medicine, 2023)
BackgroundImmune checkpoint inhibitors (ICIs) are the standard of care for metastatic cutaneous melanoma (mCM) patients, but their efficacy in young adults aged less than 40 years remains unclear.Materials and methodsWe retrospectively analyzed 303 stage IV melanoma patients of different ages treated with nivolumab, pembrolizumab, or ipilimumab plus nivolumab combination therapy. Clinical data and blood values such as LDH, CRP, and absolute immune cell counts were retrieved from the medical records. Pre-treatment serum concentrations of soluble immune checkpoint proteins were measured using ELISA. In addition, information on frequencies of various T cell subsets in the peripheral blood was collected from a previously reported study (ELEKTRA). Patient characteristics and clinical information was correlated with PFS and OS using univariate and multivariate cox regression analysis.ResultsOf 303 patients, 33 (11%) were ≤ 40 years old. The older patients had a median age of 64 (95% CI: 61-66). Concerning prognostic parameters, there was no difference between the age groups, e.g., in gender, LDH, or the existence of brain or liver metastases. Patients aged ≤ 40 years [p = 0.014; HR: 1.6 (95% CI: 1.1-2.4)], presence of liver metastases [p = 0.016; HR: 1.4 (95% CI: 1.0-1.9)], line of ICI treatment [p = 0.009; HR: 1.4 (1.0-1.9)], elevated LDH [p = 0.076; HR: 1.3 (95% CI: 0.97-1.8)], and brain metastasis [p = 0.080; HR: 1.3 (95% CI: 0.97-1.7)], were associated with shorter PFS in univariate analysis. Multivariate analysis revealed that the patient’s age (≤ 40 years) remains a high-risk factor upon adjusting for all potential confounders [p = 0.067; HR: 1.5 (95% CI: 0.97-2.3)]. Blood parameters revealed that patients ≤ 40 years have relatively higher frequencies of activated CD4 T cells (CD4 + Ki67 + CD4 + ICOS +) in the blood, and significantly lower number of basophils and CD45RA- memory T cells, compared to patients above 40 years (p < 0.05). In addition, patients ≤ 40 years experiencing disease progression within 6 months of ICI treatment had increased concentrations of sPDL1 (p = 0.05) and sTIM3 (p = 0.054) at baseline.ConclusionYoung patients with stage IV melanoma may experience shorter progression-free survival upon ICI treatment compared to patients above 40 years and are characterized by fewer basophils and memory T cells in the blood.
Gesehen am 15.03.2023